Alternating versus direct current in electrohydrodynamic drying. Issue 11 (1st August 2022) - Martynenko, Alex; Kudra, Tadeusz
Abstract: Although DC power is claimed to be more energy-efficient than AC power for EHD drying, experimental studies on this subject are still insufficient. This research compares the efficiency of DC versus AC (60 Hz frequency) power for EHD drying by using 1 × 1 and 2 × 2 multi-pin discharge electrodes. Energy indicators were determined from the measurements of electric power consumption at the corresponding drying rate of the wet tissue paper. The experiments revealed the key benefits of DC drying, such as enhanced drying rate, higher energy efficiency, and lower specific energy consumption. For the comparable drying flux of 0.2 g/(m 2 s), the specific energy consumption of DC drying was in the range from 350 J/g (2 × 2) to 750 J/g (1 × 1) as compared with 2000 J/g (2 × 2) to 5000 J/g (1 × 1) for AC. The specific energy consumption of a 2 × 2 discharge electrode was consistently smaller than the 1 × 1 one, indicating the role of emitters spacing in the process efficiency. The specific energy consumption of both electrodes increased with the drying rate.